Pengaruh Disiplin Kerja dan Beban Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Koperasi Perindustrian dan Perdagangan Kota Bima - Fira Safira; Amirulmukminin Amirulmukminin (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The objectives of this research are (1) To determine whether there is an influence of Work Discipline on Employee Performance at the Bima City Industrial and Trade Cooperative Service office, (2) To determine whether or not there is an influence of Workload on Employee Performance at the Bima City Industrial and Trade Cooperative Service office. (3) To determine whether there is an influence of Work Discipline and Workload on Employee Performance at the Bima City Industry and Trade Cooperative Service office. The population in this study were all employees at the Office of Cooperative Industry and Trade of the City of Bima, totaling 60 people. The sample was determined by purposive sampling technique with 40 respondents. Data collection methods used are observation, questionnaires (questionnaire), and literature study. The data analysis techniques used in this research are validity test, reliability test, classical assumption test, multiple linear regression, analysis of correlation coefficient and coefficient of determination, T test, and f test, using the SPSS v20 program. Based on the results of data processing using the T test and F test methods, it is known that the Work Discipline and Work Load variables simultaneously have a significant effect on employee performance at the Bima City Cooperative Industry and Trade Office. Partially, the results of this research show that the Work Discipline variable has a significant positive effect on employee performance at the Bima City Cooperative Industry and Trade Office. Meanwhile, workload has a significant negative effect on employee performance at the Bima City Cooperative Industry and Trade office.